Word of life : introducing Lutheran hermeneutics - Wengert, Timothy J. (Minneapolis, Fortress Press, 2019)
"Renowned Reformation scholar Timothy J. Wengert explores the genesis of Lutheran biblical interpretation, tracing its emergence in the early work of Martin Luther, through Melanchthon and other Wittenberg exegetes. This distinctly Lutheran approach interpreted Scripture in terms of 'law and gospel,' emphasized reading and translating the Greek and Hebrew texts, and centered on the theology of the cross and justification by faith. Luther and his colleagues found God working in the last place anyone would expect: on the cross, in weakness and foolishness. Using examples from Luther's sermons and biblical commentaries, Wengert shows how these key historical and theological perspectives can inform Lutheran preaching and teaching today" --page 4 of cover.
The cloud of witnesses -- Not "just the facts, ma'am" : from definition to effect -- The law always accuses : the Gospel always forgives -- Famous last words -- Living with the saints in the Psalms -- Appendix: Philip Melanchthon on the word justification in 1532.
Includes bibliographical references (pages 158-164).
Keywords: Luther, Martin, -- 1483-1546.; Luther, Martin, -- 1483-1546 -- Theology; Luther, Martin, -- 1483-1546 -- Influence; Melanchthon, Philipp, -- 1497-1560 -- Influence; Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc. -- History -- 16th century